Self-Organizing Seafloor mapping of the Tjörnes Fracture Zone / Iceland - Riedel, Carsten (Christian-Albrechts-Universität zu Kiel, 2002)
The Tjörnes Fracture Zone (TFZ) is a transform zone in the North Atlantic separating the Northern Volcanic Zone (NVZ) of Iceland from Kolbeinsey Ridge. The area exposes active volcanism and hydrothermalism and is subject to strong earthquakes. A reflection seismic survey has been conducted. It was complimented by gasgeochemical measurements, submersible diving and geological sampling of the seafloor. During the first part of the thesis a method is developped to detect the lithology from physical properties calculated from the acquired seismic data. The second part compares the results of the new method with the other observations and unravels the geological setting of the TFZ, in particular in Skjalfandi Bay. The final result is a map of the seafloor lithology as indicated by parameters such as reflectivity and roughness and environmental factors such as morphology, structure and sampled seafloor lithology within the Tjörnes Fracture Zone region north of Iceland.